Towards a Digital Atlas for Cultural Landscape: Framework Design and Mobile Application Development for Documenting Tangible and Intangible Heritage - Kevseroglu, Ozlem; Kurban, Rifat (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2026)
This paper introduces the Kayseri Digital Atlas project, a mobile application built with Flutter and supported by a web interface, created to document both the tangible and intangible cultural heritage of Kayseri’s Cumhuriyet Neighbourhood. Through a custom data-entry system, the project has systematically collected more than 2,000 archival and oral history records, establishing a well-structured platform that can serve as a foundation for future efforts such as AI-driven classification and digital reconstruction.